Salam (Forward sale) and Istisna' (Manufacture contract) in modern applications: a Maqasid al-shari'ah perspective - Ali, Mohammed Farid (Zes Rokman Resources, 2016)
The modern application of Salam such as parallel Salam and combination of Salam with waÑd (promise) exposes Islamic financial institutions (IFIs) to risks—credit risk, market risk, and operational risk. Modern applications of IstiÎnaÑ by financing houses and projects in the form of parallel-IstiÎnaÑ and IstiÎnaÑ based BOT (buy, operate and transfer) has exposed the IFIs to hazards such as delayed and incomplete projects. This paper explores the extent to which modern applications of Salam and IstiÎnaÑ support the maqÉÎid al-SharÊÑah. The study suggests new terms and conditions to minimise the risks if not eliminate them. It advises IFIs to become IstiÎnaÑ contractors in the real economy rather than on paper only. Salam should not be a near-replica of speculative and risky future contracts. If adjustments are not made in modern application of both contracts, the contracts risk jeopardising the very purpose of the SharÊÑah.